Managing knowledge, service innovation and service experience in hospitality industry: A proposed framework - Poh, Wai Choo; Tan, Cheng Ling; Fernando, Yudi (Academic Conferences and Publishing International Limited Reading, UK, 2018)
Organisation knowledge, customer market intelligence, intellectual capital from frontline managers and frontline employees represent the true “intangible resources/assets’’ in a Hospitality Industry (HI) organisation. These intangible resources/assets provide the creative potential for service/product innovation. Innovation is an HI organisation’s strategic and technical “know-how” in sustainable economic growth. Service/product innovation per se does not benefit a HI organisation unless it manifests current superior service experience quality value in the customer-driven marketplace. The objective of this study is to provide the theoretical justification on the strategic know-how in executing an organisation’s knowledge-based social perspective (culture, structure, human resource) and technical perspective (technology) with the collaborative support from frontline managers and frontline employees to increase the organisation service innovation. The success of service/product innovation implementation can influence high customer service experience quality (EXQ) which could help attract more tourists and increase occupancy in hotels in Malaysia. Service innovation could improve service offerings, avoid similar service failures and reduce costs in HI organisations. Without replenishing latest external customer knowledge, an HI organisation is less capable of discovering and exploiting new opportunities. This study provides 38 synthesised literature evidences via content analysis on critical factors that influence the effectiveness of knowledge management within the HI organisation, which in turn influences a successful HI organisation service innovation and high EXQ. The study aims to motivate managers/hotel industry players/future researchers in HI organisations to use innovation as a tool for strategic economic growth. The finding can be referred to as continuously exploring innovative ways to manage and leverage an organisation’s knowledge resources through internal and external network structures. This can enable the actors (frontline managers and frontline employees) to access and share diverse knowledge with each other to effect more exceptional creativity and innovation, thereby meeting EXQ. Hopefully future researchers would further investigate the potential value of systemic absorptive capacity process construct in HI service innovation.